Volatile fatty acid evolution in biomass mixture composts prepared in open and closed bioreactors - Plachá, Daniela; Raclavská, Helena; Kučerová, Martina; Kuchařová, Jana (Waste management (New York, N.Y.), 2013)
In this study we observed the production of volatile fatty acids (VFAs) during the composting process of compost heaps in two different bioreactors (open and closed) at three different depths (0, 40 and 80 cm). The compost was prepared as a mixture of bio-waste, horse manure, grass and sawdust to ensure sufficient pH conditions in compost heaps. VFA contents in the composting materials were analysed weekly over 14-119 d. The degradation process was monitored, along with temperature, pH, total organic carbon, oxidizable carbon and mono- and oligosaccharides. VFA contents were evaluated with regard to the depth of the sample site in the compost heap and to conditions in the bioreactors. The maximum VFA occurrence was observed during the first 35 d; acetic and propionic acids in particular were determined to occur in each sample. Considerable variations in their formation and elimination were observed in the two bioreactors as well as at the various depths in the compost heaps. Significant correlations were found between individual VFAs, as well as between VFA concentrations and organic carbon contents.
Keywords: Temperature; teplota; bioreaktory; Propionates; Bioreactors; odpad tekutý - odstraňování; zvířata; biomasa; půda; uhlík; koně; koncentrace vodíkových iontů; Manure; Acetic Acid; Biomass; kyselina octová; propionáty; Fatty Acids, Volatile; Horses; Animals; Carbon; hnůj; Soil; Waste Disposal, Fluid; Hydrogen-Ion Concentration; kyseliny mastné těkavé